Sub-Xiphoid Abscess and Sinus after Open Heart Surgery - Dosoky Elayouty Hamdy; H. Elayouty Ahmed (Journal of Clinical Case Reports and Images, 2022)
Purpose Is it safe to excise only the external portion of the pacemaker wires? This presentation aims to find out the proper way to manage pacing wires postoperatively. Methods We report 5-cases of sub-xiphoid abscesses and sinuses after valve surgery. Each case presented with a recurrent abscess that opens and drains its contents through a sinus around the lower-most portion of the xiphoid process. The duration between open heart surgery and evolution of these abscesses varied between 18 and 60 months. Valve surgeries were mitral and/or aortic valve replacement. Surgeons usually insert pacemaker wires to control any persistent post-operative arrhythmias that can affect hemodynamic circulation. On the day of discharge, some surgeons (not in our center) usually excise the pacemaker wires. Results The remaining intra-thoracic portions underwent some degree of corrosion that caused a state of chronic inflammation, sinus track formation and abscess evolution. This indicated radiological examination and surgical exploration to extract these foreign bodies. These 5 cases were diagnosed and operated upon between 15th January 2022 and 1st March2022, all at Abo-Khalifa Emergency Hospital-Ismailia, Egypt. Conclusions This confirms the significance of total withdrawal of the external pacemaker wires. Surgeons should not apply tight sutures at the site of insertion of the wires.
Keywords: should pacemaker wires be withdrawn as a whole